Development of control-oriented models of Dual Clutch Transmission systems - Olivi, Davide <1985> (Alma Mater Studiorum - Università di Bologna, 2013)

(untitled)
A control-oriented model of a Dual Clutch Transmission was developed for real-time Hardware In the Loop (HIL) applications, to support model-based development of the DCT controller. The model is an innovative attempt to reproduce the fast dynamics of the actuation system while maintaining a step size large enough for real-time applications. The model comprehends a detailed physical description of hydraulic circuit, clutches, synchronizers and gears, and simplified vehicle and internal combustion engine sub-models. As the oil circulating in the system has a large bulk modulus, the pressure dynamics are very fast, possibly causing instability in a real-time simulation; the same challenge involves the servo valves dynamics, due to the very small masses of the moving elements. Therefore, the hydraulic circuit model has been modified and simplified without losing physical validity, in order to adapt it to the real-time simulation requirements. The results of offline simulations have been compared to on-board measurements to verify the validity of the developed model, that was then implemented in a HIL system and connected to the TCU (Transmission Control Unit). Several tests have been performed: electrical failure tests on sensors and actuators, hydraulic and mechanical failure tests on hydraulic valves, clutches and synchronizers, and application tests comprehending all the main features of the control performed by the TCU. Being based on physical laws, in every condition the model simulates a plausible reaction of the system. The first intensive use of the HIL application led to the validation of the new safety strategies implemented inside the TCU software. A test automation procedure has been developed to permit the execution of a pattern of tests without the interaction of the user; fully repeatable tests can be performed for non-regression verification, allowing the testing of new software releases in fully automatic mode. === Un modello orientato al controllo di una trasmissione a doppia frizione (DCT) è stato sviluppato per applicazioni real-time Hardware In the Loop (HIL) come supporto allo sviluppo model-based della centralina elettronica di controllo (TCU, Transmission Control Unit). Il modello è un tentativo innovativo di riprodurre le dinamiche del sistema di attuazione, molto veloci, mantenendo un passo di simulazione sufficientemente grande per applicazioni real-time. Il modello comprende una descrizione dettagliata del circuito idraulico, delle frizioni, dei sincronizzatori e delle marce, e un modello semplificato del veicolo e del motore. Poiché l’olio che circola nel sistema ha un modulo di comprimibilità molto elevato, le dinamiche di pressione sono molto veloci, causando instabilità durante una simulazione real-time; lo stesso problema riguarda la dinamica delle servo valvole, a causa delle piccole masse degli elementi in movimento. Perciò, il modello è stato modificato e semplificato senza perdere validità fisica, per adattarlo alla necessità di una simulazione real-time. I risultati di simulazioni offline sono stati confrontati con misure effettuate in vettura per verificare la validità del modello sviluppato, che è stato poi implementato all’interno di un sistema HIL e connesso alla TCU. Una serie di test è stata eseguita al simulatore: test riguardanti guasti elettrici su sensori ed attuatori, guasti idraulici e meccanici su valvole, frizioni e sincronizzatori, e test applicativi comprendenti tutte le principali funzionalità del controllo. Essendo basato su leggi fisiche, il modello simula una reazione plausibile del sistema in ogni condizione. Il primo uso intensivo del simulatore ha portato alla validazione delle nuove strategie di safety implementate in TCU. Una procedura di automatizzazione dei test è stata sviluppata per permettere l’esecuzione di un pattern di test senza l’interazione dell’utente; test completamente ripetibili possono essere eseguiti per verifiche di non regressione, permettendo di testare nuove release software in modo completamente automatico.